Rancang Bangun Sistem Produksi dan Persediaan UMKM - Rinci Kembang Hapsari; Azmuri Wahyu Azinar; Sugiyanto Sugiyanto (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
The large contribution of MSMEs is as a driver of the nation's economy which is proven to be resistant to various shocks to the economic crisis. In operational records, MSMEs still use manual systems and there are even those that are not recorded properly. Even in the production process that functions to determine the cost of production and production control also still using manual methods. So that a computerized system is needed in the production process that can automatically calculate the cost of production, control the production and inventory stock. Based on testing and analysis, it can be proven that the applications built are very helpful to MSMEs, especially in the production process because data processing can be done quickly and accurately. With the computerized application system produced, it can monitor production results and control stock items.So that it can minimize the accumulation of goods stock production and the occurrence of empty stock for a long time. With this application system can also help MSMEs in determining the cost of production automatically.